Penerapan Problem Based Learning Berbantuan Gamifikasi Wordwall untuk Meningkatkan Hasil Belajar Panen dan Pasca Panen di SMKN 1 Gondang - Savira Putri Wulandari; Marmi Marmi; Achmadi Achmadi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This research is a Classroom Action Research (PTK) which aims to optimize student learning outcomes through the application of Problem Based Learning (PBL) on Harvest and Post-Harvest elements. The research subject used class XI ATPH 1 at SMKN 1 Gondang with a total of 32 people. The research took place in two cycles of action repeatedly with the stages of the cycle that have been determined so that the objectives are achieved. Cycle one learning activities were carried out on March 6, 2025 and cycle two was held on April 17, 2025. The cycle consists of planning, action implementation, observation, and reflection stages. Data collection techniques through formative assessment / post test. This study shows the results that the application of the PBL model succeeded in improving the learning outcomes of students who previously had a value at the pre-cycle stage with an average of 46.56 increasing to 75.78 in cycle one and cycle two with an average of 80.47. Based on these results, it can be concluded that the application of the PBL model improves the learning outcomes of students on harvest and post-harvest elements.